Knowledge, attitudes, and practices regarding asthma management among pharmacists in palestine: A cross-sectional study - Dima Masri; Haneen Joulani; Alisse Nasser; Dala N. Daraghmeh (PLoS ONE, 2026)
Background Pharmacists can play a key role in asthma management through patient education, inhaler technique assessment, and promoting evidence-based care. This study assessed Palestinian pharmacists’ general asthma knowledge, asthma pharmaceutical care knowledge, attitudes, practices, and perceived barriers to asthma management. Methods A cross-sectional study was conducted from March to June 2025 in Palestine. Data were collected using a self-administered online questionnaire (convenience/volunteer-response sampling; response rate not determinable). General asthma knowledge was scored by awarding 1 point per correct response (range 0–17) and categorized as poor (0–8), fair (9–11), and knowledgeable (12–17). Data were analyzed using SPSS, bivariate associations were tested using chi-square test, or Fisher’s exact test, and multivariable linear regression was used to identify independent predictors. A p-value of < 0.05 was considered statistically significant. Results A total of 402 participants (137 male and 265 female) participated in this study. Overall, 57.2% were classified as knowledgeable in general asthma knowledge. Pharmacists working in hospital settings showed a significantly higher asthma knowledge in comparison with those working in community pharmacies (β = 0.110, p = 0.032). However, the model explained minimal variance (R² = 0.037) and was not statistically significant overall (overall model p = 0.144). No pharmacists’ characteristics were significantly associated with asthma pharmaceutical care knowledge (R² = 0.027; overall model p = 0.378) or attitudes and practices (R² = 0.014; overall model p = 0.850). Conclusion Pharmacists demonstrated mixed asthma knowledge with gaps relevant to updated guideline-based care, alongside practice barriers and clinically important practice gaps. Given the very low R² values, observed associations should be interpreted cautiously. Structured continuing professional development and targeted training may improve pharmacists’ uptake of updated recommendations and strengthen asthma pharmaceutical services.